Zirconia nanotube coatings - UV-resistant superhydrophobic surfaces - Raghu, Swathi Naidu Vakamulla; Chuluunbandi, Khajidkhand; Killian, Manuela (Surfaces and Interfaces, 2021)
Surface modifications influence material interactions such as wettability, imparting hydrophobicity or hydrophilicity. Mainstream research focused on enhancing product shelf-life directs attention towards superhydrophobic surfaces (SHS). SHS offer several benefits for out-door applications such as self-cleaning, antisoiling, anti-mist etc. Recently, such surfaces were created by hydrophobization of anodized titania, which although effective lacked a long-term stability of their hydrophobic modifications due to it being susceptible to UV-mitigated degradation. In light of this situation, ZrO2-nanotubes are evaluated with regard to their application as transparent UV-stable superhydrophobic coatings. Nanostructured oxide surfaces are created via singlestep electrochemical anodization. The absence of HF acid-based pre-etching steps offer a safe and alternatively a green synthesis route. Anodized oxides are modified using octadecylphosphonic acid (OPA) self-assembled monolayers, demonstrate superhydrophobicity and are at par with conventionally employed coatings such as PTFE, PFDPA and PTES. The OPA-coatings are evaluated for their mechanical stability under a jet of water, chemical stability under indirect sunlight irradiation in air/water and direct UV exposure. Zirconia nanotubular films were evaluated for optical transparency using light microscopy and surface wettability of the different zirconia-composites was compared to the model system - titania. Structural and compositional differences of the SAM layer upon time dependent decay were analyzed with X-ray photoelectron spectroscopy.
CRIS-Team WoS Importer:2021-10-08